(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
Abnormal uterine bleeding (AMB) is a general term used to describe uterine bleeding that exceeds the volume and duration of normal menstruation in women of reproductive age (Fraiser I.S., Langham S., 2009). Abnormal uterine bleeding occurs in 14-25% of women of reproductive age (Adamyan L.V., Sibirskaya E.V., Koltunova I.E., 2016) and can have a significant impact on their physical, social, emotional and material quality of life. Abnormal uterine bleeding in reproductive age is associated with various types of functional and organic disorders of the reproductive system of women. In particular, one of the most common causes is a violation of the ratio of estrogens and progestogens that affect the target tissue - the endometrium, therefore, according to the classification of The International Federation of Gynecology and Obstetrics (FIGO), they are registered as AMK-O. According to the PALM-COEIN classification system, which is a mnemonic for structural (PALM) and non-structural (COEIN) causes of abnormal bleeding, non-gravid urgent uterine bleeding due to ovulatory dysfunction (AUB-O) is abnormal, which, according to gynecological examination and ultrasound, cannot be explained by the usual causes of bleeding (structural gynecological abnormalities, cancer, inflammation, systemic diseases, oral contraceptives or certain drugs).